Meeting of Chief Secretaries on Implementation of Economic Stimulus Measures Background Papers (Volume II) - Planning Commission (Planning Commission, 2009)
Points for discussion with Chief Secretaries of the State Governments pertaining to Railway Projects. A large number of projects have been undertaken by Indian Railways throughout the country. These projects include New Line, Gauge Conversion, Doubling, Railway Electrification and Metropolitan Transport Projects. During implementation, State Government assistance is required on various issues and without their help, it is impossible to complete the project in a prescribed time frame. The issues concerned with the State Government are given in the enclosed brief, however, there are certain general issues for which state Governments are requested to render necessary assistance.
Government of India Planning Commission
Government of India Planning Commission